GENETIC DIVERSITY OF AMPICILLIN-RESISTANT Vibrio ISOLATED FROM VARIOUS STAGES OF TIGER SHRIMP LARVAE DEVELOPMENT - WIDANARNI WIDANARNI; ANTONIUS SUWANTO (SEAMEO BIOTROP, 2000)
This research was carried out to study genetic diversity of ampicillin-resistant Vibrio from various stages of tiger shrimp larvae (Penaeus Monodon) development from,Tambak Inti Rakyat hatchery, near Labuan, West Java, Indonesia. A total of 25 ampicillin-resistant Vibrio isolates were isolated using thiosulphate citrate bile-salt sucrose agar (TCBS-Agar) and seawater complete agar (SWC-Agar). Physiological and biochemical characterization showed that the isolates could be grouped into only two species, i.e. V. harveyi from the egg stage; and V. metschnikovii from larvae and post-larval stage (i.e nauplius, zoea, mysis, PLi, PL5, PL,0, and PL,5). These isolates were also present in their respective rearing water of each stage and some natural feed. Schizotyping analysis employing restriction endonuclease Noll (5'-GC4GGCCGC) indicated that the isolates could be grouped into at least 13 different genotypes. Therefore, schizotyping was more discriminative than physiological characterization. This study showed that particular groups of Vibrio colonized all stages of shrimp larvae and demonstrated closed phylogenetic relationship. These groups of Vibrio might be the dominant microbiota which could suppress the development of other Vibrio including the pathogenic Vibrio. Key words : Shrimp/ampicillin-resistant K/fcno/schizotyping